Modeling solar wind with boundary conditions from interplanetary scintillations. (September 2015) - Manoharan, P; Kim, T; Pogorelov, N V; Arge, C N; Manoharan, P K
Abstract: Interplanetary scintillations make it possible to create three-dimensional, time- dependent distributions of the solar wind velocity. Combined with the magnetic field observations in the solar photosphere, they help perform solar wind simulations in a genuinely time-dependent way. Interplanetary scintillation measurements from the Ooty Radio Astronomical Observatory in India provide directions to multiple stars and may assure better resolution of transient processes in the solar wind. In this paper, we present velocity distributions derived from Ooty observations and compare them with those obtained with the Wang-Sheeley-Arge (WSA) model. We also present our simulations of the solar wind flow from 0.1 AU to 1 AU with the boundary conditions based on both Ooty and WSA data.